Survei Route Determination Using The Saving Matrix Method (PT. Indekstat Konsultan Indonesia) - Maghfiroh, Amalia Ma'rifatul; Karim, Ahmad Alfianul (Universitas Nusantara PGRI Kediri, 2023)
Research aim : The aim of this research is to calculate the optimal survey route and minimizing route. This study focuses on the route to meeting sample respondents of the Bojonegoro regency government service community satisfaction survey. Design/Methode/Approach : Data collection is done by collecting data secondary in the company. Data processing is done by the Saving method Matrix Research Finding : From the results of data processing and processing of the company's initial survey route, that is equal to 1772,9 KM and the total distribution distance using the saving matrix method and the nearest insert method is 1323,2 KM with a distance saving value of 449,7 KM. Theoretical contribution/Originality : Saving Matrix is ​​a technique used to schedule a limited number of vehicles from a facility and the number of vehicles in this fleet is limited and they have different maximum capacities. The aim of this method is to choose the best possible vehicle assignment and routing (Bowersox, 2002). Research limitation :: More than 400 sample locations of respondents in a community satisfaction survey project for Bojonegoro district government services. The research limitation is that the selected village location points are limited to only one village at the northernmost point in a sub-district and one village at the southernmost point in a sub-district.